Sudan after the Naivasha peace agreement: No champagne yet - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2005)
A peace agreement for Sudan was signed in Nairobi on January 9, 2005. The accord opens a historic opportunity to end the conflict between the Sudanese government and the SPLA rebels in southern Sudan. The cornerstones of the deal are political autonomy for southern Sudan during a transitional period leading up to a 2011 referendum on independence for the South, and equal sharing of oil revenues. The peace agreement is, however, merely the first step toward settling the conflict. The two sides must now get on with the much tougher challenge of implementation, which will be doomed to failure without an active long-term commitment by the international community. Impetus for a peace process for the country as a whole - and thus also an end to the conflict in Darfur - is not to be expected from these developments. (SWP comments / SWP)
Keywords: 320